Media representation of migrant and refugee populations and public discourse during two crises in Greece between 2020-2022: Migratory movements at the greek-turkish land borders in Evros and the covid-19 pandemic - Georgikopoulou, Christina; Fouskas, Theodoros (Comparative Cultural Studies: European and Latin American Perspectives, 2025)
Introduction: Public discourse, whether it concerns the dominant political discourse or the media of mass opinion formation, can become the determinants of positive or negative impressions, while it is observed that in recent years their role regarding refugees and migrants has been mainly negative. In February 2020, the flow crisis at the Greek-Turkish border (Evros) began when refugees and migrants attempted to cross the Greek border in their effort to enter Europe. The migratory movement crisis at the Evros border point of entry was followed by a second crisis, the COVID-19 pandemic. The article aims to examine the representation of migrant and refugee populations in public discourse in Greece between 2020-2022 during the two crises, those of the migratory movements at the Greek-Turkish land borders in Evros and the health crisis of the COVID-19 pandemic. Methodolgy: Systematic literature review of the research carried out in studies that have taken place regarding the representation of refugees and immigrants in public discourse during two crises, for the period 2020-2022. This work takes into account all the studies, in English and Greek, that have been carried out with the specific keywords, for the aforementioned period. Results: It emerges from the literature review that in public discourse, both in political discourse and in the mass media and social media, in newspapers and in social networks, that refugees and migrants are mainly portrayed negatively regarding a) the migratory movement crisis at the border entry point of Evros in February-March 2020 and b) during the public health crisis. Discussion: Refugees and migrants are depicted/represented as “invaders”, as “dangerous” and the “harmful elements”, as an asymmetric threat to national security, the socio-political community and public health.